2002
DOI: 10.1063/1.1463442
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of line mixing in NH3 spectra. I. Scaling analysis of parallel bands perturbed by He

Abstract: Articles you may be interested inCritical interpretation of CH-and OH-stretching regions for infrared spectra of methanol clusters (CH3OH) n (n = 2-5) using self-consistent-charge density functional tight-binding molecular dynamics simulations A laboratory and theoretical study of protonated carbon disulfide, HSCS +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Previous semiclassical theoretical models qualitatively describe the self-broadenings [1] but strongly exaggerate the J À K dependence for the non-polar buffers [2,28,34]. Empirical polynomial models [15,16] based only on J and K also have difficulty representing self-broadening at low J, and the Q-branch broadenings for non-polar buffer gases.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous semiclassical theoretical models qualitatively describe the self-broadenings [1] but strongly exaggerate the J À K dependence for the non-polar buffers [2,28,34]. Empirical polynomial models [15,16] based only on J and K also have difficulty representing self-broadening at low J, and the Q-branch broadenings for non-polar buffer gases.…”
Section: Discussionmentioning
confidence: 93%
“…The self shifts are one to two orders of magnitude smaller than the self-broadenings, and, where determinable, their signs depend on the inversion symmetry. Inclusion of line mixing in first order permits us to extend the fits to higher pressure, but a full relaxation matrix inversion [6,7,19,34] may be required at even higher pressure. The opposite signs and nearly equal magnitudes of the f m for the m 1 and m 3 s À a tunneling partners are another indication of the dominant coupling for self-broadening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hadded et al [13] have studied line mixing of 15 inversion doublets of NH 3 perturbed by He, Ar, and H 2 . More recently, these authors [14,15] have measured line mixing effects in the m 1 and m 2 bands of NH 3 at high pressure. They have demonstrated the necessity of take into account line mixing for the treatment of inversion-rotation spectra of NH 3 .…”
Section: Introductionmentioning
confidence: 97%
“…In other studies, it was shown that line mixing could greatly influence the values of the molecular parameters obtained during fitting processes with assumed line shapes. In fact, line mixing was also taken into accounted in several studies for the m 1 , m 2 , and m 4 bands of NH 3 perturbed by He, Ar and H 2 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%